2022
DOI: 10.1002/ctm2.780
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐transmitted miR‐769‐5p confers cisplatin resistance and progression in gastric cancer by targeting CASP9 and promoting the ubiquitination degradation of p53

Abstract: Background Cisplatin resistance is the main cause of poor clinical prognosis in patients with gastric cancer (GC). Yet, the exact mechanism underlying cisplatin resistance remains unclear. Recent studies have suggested that exocrine miRNAs found in the tumor microenvironment participate in tumor metastasis and drug resistance. Methods Exosomes isolated from BGC823 and BGC823/DDP culture medium were characterized by transmission electron microscopy and differential ultracentrifugation, and miRNA expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Over the past decades, considerable attention has been paid to the effect of EV-mediated drug resistance. , However, the drug resistance caused by cell-to-cell transmission through EVs still needed to be further explored. Through the above off-chip experiments, we verified that EVs are the main factor inducing drug resistance in susceptible cells.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, considerable attention has been paid to the effect of EV-mediated drug resistance. , However, the drug resistance caused by cell-to-cell transmission through EVs still needed to be further explored. Through the above off-chip experiments, we verified that EVs are the main factor inducing drug resistance in susceptible cells.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al revealed that the TNFRSF1A might exert as a prognosis and immune infiltration biomarker for the glioblastoma multiforme ( Wang et al, 2022b ). Using a cellular mechanism that involves targeting CASP9 and enhancing the ubiquitination degradation of p53, Jing et al observed the exosome-transmitted miR-769-5p imparts cisplatin resistance and gastric cancer progression ( Jing et al, 2022 ). Li et al revealed that LINC00607 could facilitate thyroid cancer progression by regulating the CASP9 promoter methylation ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 112 ] Jing et al suggest that miR‐769‐5p is highly expressed in serum exosomes of cisplatin‐resistant patients and exosomal miR‐769‐5p targets CASP9 to suppress caspase pathway activation and p53 stability. [ 113 ] Exosomal miR‐501 confers resistance to DOX in sensitive gastric cancer cells via inhibition of apoptosis and exosomal miR‐155‐5p from PTX‐resistant gastric cancer cells induce chemoresistance in the sensitive cells by targeting GATA3 and TP53INP1. [ 114 ] The levels of exosomal miR‐1238 are higher in TMZ‐resistant GBM cells than sensitive cells and exosomal miR‐1238 induces TMZ resistance by targeting caveolin‐1.…”
Section: Evs and Cancer Drug Resistancementioning
confidence: 99%